2009
DOI: 10.1364/oe.17.022861
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and collimated blue light generated by four-wave mixing in Rb vapour

Abstract: We investigate frequency up-conversion of low power cw resonant radiation in Rb vapour as a function of various experimental parameters. We present evidence that the process of four wave mixing is responsible for unidirectional blue light generation and that the phase matching conditions along a light-induced waveguide determine the direction and divergence of the blue light. Velocity-selective excitation to the 5D level via step-wise and two-photon processes results in a Doppler-free dependence on the frequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
102
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 16 publications
9
102
0
1
Order By: Relevance
“…by dropping the two-level absorption term from Eq. (12), such that only the ladder-transparency term…”
Section: Controlled Propagation Dynamics Of Cross-talkmentioning
confidence: 99%
See 2 more Smart Citations
“…by dropping the two-level absorption term from Eq. (12), such that only the ladder-transparency term…”
Section: Controlled Propagation Dynamics Of Cross-talkmentioning
confidence: 99%
“…With an additional control field coupling to a fourth atomic level, the χ (3) process can significantly affect the dispersion [6] and absorption [7,8] properties of the probe field. The efficient parametric generation of a four wave-mixing (FWM) field using the resonant χ (3) process in a four-level double-ladder atomic system has been recently demonstrated [6,[8][9][10][11][12][13][14]. In particular, this system allows efficient frequency up-conversion [10][11][12] and down-conversion [13,14] through the use of low-power continuous-wave lasers that can be used for ultraviolet generation and quantum communication [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, complex light-atom interaction has been induced in three-level atomic media using electromagnetically induced transparency [2,3], electromagnetically induced absorption [3,4], coherent trapping of atomic populations [5], and quantum interference between atomic energy levels [6]. These coherent processes have been the basis for highly sensitive magnetometers [7,8], quantum information processing using Kerr-type nonlinearities [9], efficient photon-counting [10,11], frequency up-conversion using atomic vapors [12,13], lasing without population inversion [6], and highly compact frequency standards [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since then it has become an active area of research of several groups [3,4,5,6,7] and has been even suggested for advanced undergraduate laboratories [8]. The technique is of interest because new optical field generation in atomic media can lead to important applications in quantuminformation science [9] and low atom number detection [10].…”
Section: Introductionmentioning
confidence: 99%